Female Body Dissatisfaction and Attentional Bias to Body Images Evaluated Using Visual Search - Cass, John; Giltrap, Georgina; Talbot, Daniel (Frontiers in Psychology, 2020)
A compound visual search task was used to investigate the relationship between body dissatisfaction and attentional biases to images of underweight and obese female bodies. Seventy-one undergraduate females, varying their degree of body dissatisfaction and Body Mass Index (BMI), searched for a horizontal or vertical target line among tilted lines. A separate female body image was presented within close proximity to each line. On average, faster search times were obtained when the target line was paired with a uniquely underweight or obese body relative to neutral (average weight only) trials indicating that body weight-related images can effectively guide search. This congruent search effect was stronger for individuals with high eating restraint (a sub-component of body dissatisfaction) when search involved uniquely underweight bodies. By contrast, individuals with high BMIs searched for lines more rapidly when paired with obese rather than underweight bodies, than did individuals with lower BMIs. For incongruent trials, search times were indistinguishable from neutral trials, indicating that the deviant bodies neither compulsorily ‘captured’ attention nor reduced participants’ ability to disengage their attention from either underweight or obese bodies. These results imply the existence of attentional strategies which reflect one’s current body and goal-directed eating behaviours.